Experience of youth employment in international practice (The Journal of Psychology and Sociology, 2020)
The main purpose of the article is to analyze the problems of employment and youth employment in the practice of developed countries. Since the problem of unemployment and youth employment is a problem not only in Kazakhstan, but also at the world level. This urgency of the problem determines the need to analyze the best national practices for youth employment, including legislative, organizational and financial initiatives implemented in recent years. The article examines the experience of career coaching widely used in universities in the United States, the practice of retraining the unemployed     in Germany, strategies and programs to expand employment opportunities for young people in France such as “New services – jobs for young people”,”Jobs in state universities for young people”. The article also presents statistics on the unemployment rate of countries in recent years. The analysis suggests the introduction and use of some models that are effectively implemented in the field of youth employment from foreign practice, to solve the problems of employment of Kazakhstani youth. It is the Japanese«Baito» model and the US employment model «Career coaching in higher education - targeted training». However, when implementing the above-mentioned foreign experiences, it is mandatory to take into account both the General processes and the specifics of the country.Key words: youth, employment, international experience, labor market.